Jurisdiction regarding a civil claim for damages for the claim security in Regulation (EU) No 1215/2012 - Golak, Mateusz Wiktor (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
The article is devoted to national court powers in cases for damages for the claim security in Regulation (EU) No 1215/2012. The paper presents basic information about general provisions and special jurisdiction. The study is focused on damages for the claim security in the Polish civil procedure and the essentially legal meaning of tort, delict or quasi-delict in European civil law. An interpretation of the aforementioned subjects in the jurisdiction of Polish courts and the Court of Justice is presented. The author tries to answer the question of whether a person domiciled in one Member State may be sued in another Member State as regards as a civil claim for damages for the claim security awarded and carried out in another Member State.